PENGUATAN PENDIDIKAN SOSIAL KEAGAMAAN MELALUI KAJIAN FIQH AN-NISYA’ BAGI IBU-IBU PEMBINAAN KESEJAHTERAAN KELUARGA (PKK) DI DESA LARANGAN PERRENG PRAGAAN SUMENEP - Mohammad Firdaus (Universitas Al-Amien Prenduan, 2023)
Community Empowerment Practices is a learning activity for students to get important lessons from the community. In this case, empowerment in Larangan Perreng Village is more focused on the socio-religious and education sector. The goal to be achieved in this activity is to create an